Contextualization of the Concept of Nusyūz in Indonesian Marriage Law: Critical Discourse Analysis - Asmaul Husna; Mustaming; Beddu, Rahmawati (Institut Agama Islam Negeri Palopo, 2024)
This research examines the contextualization of the concept of nusyūz in marriage law in Indonesia and the implications for its resolution regarding the act of beating through a discourse analysis approach. The main focus of the research is to analyze how the interpretation and application of the concept of nusyūz originating from Islamic law is adapted in the context of modern Indonesian marriage law, especially regarding the